Pertanggungjawaban Indonesia Sebagai Negara Peratifikasi Konvensi Perlindungan Hak-Hak Seluruh Pekerja Migran Dan Anggota Keluarganya - Zati Rizqi Muhammad (Faculty of Law, Universitas Airlangga, 2024)
Abstract Indonesia has ratified the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICMW 1990) through Law Number 6 of 2012. Due to this ratification, Indonesia has various obligations to protect migrant workers entering the country to their jurisdiction regardless of their migration status under the agreement's contents. However, in practice, the Indonesian government has not taken the protection of migrant workers seriously, wildly irregular migrant workers. Therefore, the formulation of the problem includes the protection of foreign migrant workers in Indonesia and the legal consequences for Indonesia if it does not protect migrant workers under the agreement's contents. Therefore, this research is normative juridical research using a statutory and conceptual approach. Keywords: ICMW 1990, immigration status, migrant workers Abstrak Indonesia telah melakukan ratifikasi International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICMW 1990) melalui Undang-Undang Nomor 6 Tahun 2012. Konsekuensi dari melakukan ratifikasi ini, Indonesia dibebankan berbagai kewajiban untuk melindungi pekerja migran yang masuk ke wilayah hukumnya tanpa melihat status migrasinya sesuai dengan isi perjanjian. Namun pada prakteknya, Pemerintah Indonesia belum melakukan perlindungan pada pekerja migran dengan serius, khususnya pekerja migran irregular. Rumusan masalah antara lain perlindungan pekerja migran asing di Indonesia serta akibat hukum Indonesia bila tidak melakukan perlindungan pekerja migran sesuai dengan isi perjanjian. Penelitian ini merupakan penelitian yuridis normatif menggunakan pendekatan perundang-undangan (statute approach) serta pendekatan konseptual (conseptual approach). Kata Kunci: ICMW 1990, status migrasi, pekerja migran